Hubungan Nyeri Persalinan Sectio Caesarea Terhadap Terjadinya Depresi Postpartum Pada Ibu Primipara di RSUD Kota Yogyakarta - J Nugrahaningtyas W Utami; Chici Riansih; Muhammad Untung; Herta Meisatama; Khairul Imam (Medika Respati : Jurnal Ilmiah Kesehatan, 2020)
Background: Depression is very common in women, especially  on reproductive age. It is estimated that 14% -23% of pregnant women experience depression during pregnancy, and 5% -25% experience postpartum depression. Mothers with caesarean sectio labor experience high scale pain during the first 24 hours. Objective : this study aims to analyze the relationship between caesarean section labor and postpartum depression in primiparous mothers. Methods: The research method used is descriptive analytic with cross-sectional approach. The sample in this study were 20 postpartum caesarean mothers in Yogyakarta City Hospital taken by purposive sampling. Data collection tools in this study are using the Numeric Category Scale (NCS) questionnaire to measure the level of neyri and the Edinburgh Postnatal Depression Scale (EPDS) to measure the level of depression of respondents. Analysis using the Chi-Square correlation test.  Results: Most of the level of pain in postpartum SC mothers is in the moderate category that is there are 9 people or (45.0%). Most postpartum mothers in the moderate depression category were 9 people or (45.0%). Statistical results with the Chi Square test showed that there was a significant relationship between labor pain in caesarean section and postpartum depression in primiparous mothers with (p-value = 0.002) (p <0.05). Conclusion: There is a relationship between labor pain in caesarean section and postpartum depression in primiparous mother.